Preeclampsia-Associated lncRNA INHBA-AS1 Regulates the Proliferation, Invasion, and Migration of Placental Trophoblast Cells - Sijia Jiang; Qian Chen; Haihua Liu; Yue Gao; Xiaoxue Yang; Zhonglu Ren; Yunfei Gao; Lu Xiao; Mei Zhong; Yanhong Yu; Xinping Yang (Molecular Therapy: Nucleic Acids, 2020)
Preeclampsia is believed to be caused by impaired placentation with insufficient trophoblast invasion, leading to impaired uterine spiral artery remodeling and angiogenesis. However, the underlying molecular mechanism remains unknown. We recently carried out transcriptome profiling of placental long noncoding RNAs (lncRNAs) and identified 383 differentially expressed lncRNAs in early-onset severe preeclampsia. Here, we are reporting our identification of lncRNA INHBA-AS1 as a potential causal factor of preeclampsia and its downstream pathways that may be involved in placentation. We found that INHBA-AS1 was upregulated in patients and positively correlated with clinical severity. We systematically searched for potential INHBA-AS1-binding transcription factors and their targets in databases and found that the targets were enriched with differentially expressed genes in the placentae of patients. We further demonstrated that the lncRNA INHBA-AS1 inhibited the invasion and migration of trophoblast cells through restraining the transcription factor CENPB from binding to the promoter of TNF receptor-associated factor 1 (TRAF1). Therefore, we have identified the dysregulated pathway “INHBA-AS1-CENPB-TRAF1” as a contributor to the pathogenesis of preeclampsia through prohibiting the proliferation, invasion, and migration of trophoblasts during placentation.